Decentralization and Public Procurement Performance: New Evidence from Italy - Chiappinelli, Olga (Economic inquiry, 2020)
We exploit a new dataset based on European Union (EU) procurement award notices to investigate the relationship between the degree of centralization of public procurement and its performance. We focus on the case of Italy, where all levels of government, along with a number of other public institutions, are involved in procurement and are subject to the same EU regulation. We find that (a) municipalities and utilities, which currently award among the largest shares of contracts, achieve lower rebates than other institutional categories; and (b) decentralization implies lower rebates only when it comes with weak competences of procurement officials. The evidence seems to suggest that a reorganization of the procurement system, both in terms of partial centralization and increased professionalization of procurement officials, would help improve award-stage procurement performance.